(untitled) (Research, Society and Development, 2023)
Introduction: It is indispensable that the dental surgeons during their graduation show abilities and skills for the diagnosis and treatment of oral cancer, however, it is not always observed. Objective: Map the evidence of dentistry students’ knowledge about oral cancer, summarize and disclose the respective conclusions of the already performed studies and available in the databases of the world literature. Methodology: Review of scope of literature to answer the question: “What is the knowledge of dentistry students about oral cancer in the world context?”, using the basis LILACS, PubMed, SciELO and Cochrane Library, with the descriptors: oral neoplasms; oral cancer; dentistry students; early detection of cancer; early diagnosis of cancer. Portuguese and English languages. Results: The research identified 678 studies, 29 being selected and included in the review. In most of studies, the students have shown insufficient knowledge about oral cancer and its related factors, but at the same time, they have shown interest on learning more about the subject. Smoking was properly associated as the most important etiological factor for the disease, but the other factors were not clearly recognized by the students. Most of the studies about the subject were done in the Asian continent. Conclusion: The results have shown insufficient knowledge of dentistry students about etiology, diagnosis and oral cancer treatment.